Educative performance transitions in engineering students through the COVID-19 pandemic - Vázquez-Sánchez, Agustín; Delgado, Francisco (Frontiers in Education, 2023)
Higher education is a multivariable system by nature; thus, it is a complex task to maintain consistent academic success for students. This is a key factor to understand the positive and negative effects generated by the COVID-19 lockdown, particularly during the current stage of the "New Normal" period. The research presented herein considers a set of variables corresponding to students and faculty as causal factors to track, analyze, and assess the impact on the academic performance of engineering students in an urban Mexican university in both periods: online teaching during lockdown, and returning to face-to-face learning during the "New Normal".Through a hybrid survey, looking for representative learning styles, academic personality traits, and technology competencies, academic performance in both periods has been recorded along with each student's learning preference. The suggested analysis model sought correlations in the stated causal factors to find valuable behavioural patterns. The outcomes show that good students in both models have attained a high level of adaptation and feel competitive in them.On the contrary, students with lower adaptation have shown poor academic performance in both models, but they perceived the online model as the less effective learning environment.Particularly, personality traits appoint on a notable impact on performance. In addition, learning styles are not significant. Still, it has been suggested this situation could be due to a greater diversity of teaching approaches established by the faculty to take care of student performance.